Cultural materialism : theory and practice - Wilson, Scott, 1962- (Oxford, UK ; Cambridge, Mass : Blackwell, 1995)
This book attempts to explain and demonstrate the power of these modes of critical inquiry and explores their limitations.
Keywords: Shakespeare, William, -- 1564-1616 -- Political and social views; English literature; Politics and literature; Literature and anthropology; Social change in literature; Materialism in literature; Wilde, Oscar, -- 1854-1900 -- Political and social views; English literature -- Early modern, -- 1500-1700 -- History and criticism -- Theory, etc; Politics and literature -- Great Britain -- History -- 16th century